Handbook of Mechanical Engineering Calculations 26.12: True Unit Time, Minimum Lot Size and Tool-Change Time - Mitra, Rana (McGraw-Hill's AccessEngineering., 2013)
This video demonstrates how to calculate the machine unit time, the most economical machine to use, the minimum lot size, and the unit tool changing time for any type of machine tool used in metalworking operations.